Dysfunctions of brain oxytocin signaling: Implications for poor mothering. (15th June 2022) - Sanson, Alice; Bosch, Oliver J.
Abstract: Good mothering has profound impact on both the mother's and the young's well-being. Consequently, experiencing inadequate maternal care – or even neglect – in the first stages of life is a major risk factor for the development of psychiatric disorders, and even for poor parenting towards the future offspring. Thus, understanding the neurobiological basis of maternal neglect becomes crucial. Along with other neurotransmitters and neuropeptides, oxytocin (OXT) has long been known as one of the main modulators of maternal behavior. In rodents, disruptions of central OXT transmission have been associated with poor maternal responses, like impaired onset of nursing behaviors, and reduced care and defense of the pups. Importantly, such behavioral and molecular deficits can be transmitted through generations, creating a vicious circle of low-quality maternal behavior. Similarly, evidence from human studies shows that OXT signaling is defective in conditions of inadequate mothering and child neglect. On those premises, this review aims at providing a comprehensive overview of animal and human studies linking perturbed OXT transmission to poor maternal behavior. Considering the important fallouts of inadequate maternal responses, we believe that unraveling the alterations in OXT transmission might provide useful insights for a better understanding of maternal neglect and, ultimately, for future intervention approaches. Highlights: Increased brain oxytocin signaling peripartum facilitates maternal behavior. In turn, disrupted oxytocin signaling impairs aspects of maternal behavior. Poor mothering can be transmitted to female offspring. Early experience of neglect affects brain oxytocin system development. In humans, an altered oxytocin system can promote poor mothering.